TINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG ANTIBIOTIK DI KELURAHAN MANDAILING KECAMATAN TEBING TINGGI KOTA - Septiana, Lilik; Hafizhatul Abadi; Sipahutar, Rizki Anjani; Zulmai Rani (FARMASAINKES: JURNAL FARMASI, SAINS, dan KESEHATAN, 2025)
Antibiotics are a group of compounds, both natural and synthetic, that have the effect of suppressing or stopping a biochemical process in an organism, especially in the process of infection by bacteria. This study only describes the object of the study by collecting questionnaire data from the community to determine the knowledge and attitudes of the community about antibiotics in Mandailing Village, Tebing Tinggi District, City. The results of the study obtained from univariate analysis found that the level of knowledge of respondents in the high category was 34 people (35.79%), in the moderate category was 47 people (49.47%), and in the low category was 14 people (14.74%). The total score was 680. At the level of attitude, respondents in the good category were 21 people (22.10%), in the sufficient category were 22 people (23.16%), and in the less category were 52 people (54.74%); the total score was 529. At the level of community knowledge, it was in the moderate category (71.57%), community attitudes were in the less category (55.68%), and there was a relationship between age, education, and occupation with the level of knowledge; there was a relationship between education and occupation with community attitudes about antibiotics; there was a relationship between the level of knowledge and community attitudes about antibiotics in the use of antibiotics in Mandailing Village, Tebing Tinggi District, City.